The effect of Jasmine Aromatherapy and Back Massage to Reduce the Intensity of Labor Pain in the Active Phase in Maternity Hospital Ngadilah, Malang City - Wulandari, Anggrawati; Rohmah, Miftakhur; Natalia, Shanty (International Journal of Psychosocial Rehabilitation, 2020)
Labor pain is a physiological pain that is experienced by a mother. Jasmine aromatherapy and back massage can probably reduce pain, and stress. The sedatives (linalool) in the aroma of jasmine will stimulate the hypothalamus to reduce pain. This study aims to determine the effect of jasmine aromatherapy and back massage on labor pain when used in the active phase of childbirth. The method used in this study was a pre-experimental design with a one group pre-test post-test. The sample was taken through total sampling from 10th -26th August 2019. The population consisted of birthing mothers from Maternity Hospital Ngadilah in Malang city. The number of samples taken totaled 30 respondents. Pain intensity was measured using a numeric rating scale. The data analysis was conducted using the Wilcoxon test with an Asymp. Sign (0.00 <0.05). The results of the analysis showed a value of p <0.00. There were differences in the average intensity of pain when in the active phase of labor before and after being given aromatherapy using jasmine and a back massage. There is an effect because the endorphin compounds in the jasmine aromatherapy and back massage can provide comfort to the mother and eliminate pain. Hopefully this method can be applied to maternity wards by health workers.